Topical Problems of Lawmaking and Law Enforcement Pertinent to the Imposition of Criminal Punishment in the Republic of Kazakhstan - SAKENOVA, Assemgul Bolatovna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The article deals with the legal theoretical and practical concerns associated with the imposition of punishment. The imposition of punishment as a legal category has been widely studied in the literature by national and foreign scientists – experts in the field of criminal law. However, despite the importance of the principle of justice not only for the convicted person, but for the whole society, this institution of criminal law is still one of the most problematic. The problems existing in this area are affecting the law enforcement activity as a whole, evoking a negative reaction in the society. Therefore, they have reasonably attracted heightened attention of criminologists, experts in the field of criminal law and process. The objective of this article is to search for opportunities to resolve the most pressing problems associated with the imposition of punishment. The author believes that the courts of the Republic of Kazakhstan make a huge number of errors in the imposition of punishment primarily because this process has not been adequately regulated in the national legislation and the dispositions and sanctions of certain legal norms have not been accurately defined both technically and legally. The courts’ difficulties with the imposition of punishment are believed to result from the lack of understanding of the principles and criteria for the imposition of punishment. All this is believed to entail a violation of the principle of justice enshrined in Article 52, Part 1 of the Criminal Code of the Republic of Kazakhstan. The article discusses regulations, scientists’ opinions and the law enforcement practice. A clear and detailed normative regulation of the principles and criteria for the imposition of punishment to significantly limit the judicial discretion has been proposed as one of the ways to solve the problems concerned.